Faecal calprotectin testing for differentiating amongst inflammatory and non-inflammatory bowel diseases: systematic review and economic evaluation - N Waugh (Health Technology Assessment, 2013)
Background: Irritable bowel syndrome (IBS) is common, and causes pain, bloating and diarrhoea and/or constipation. It is a troublesome condition that reduces the quality of life but causes no permanent damage. Inflammatory bowel disease (IBD) comprises mainly ulcerative colitis (UC) and Crohn’s disease (CD). Both cause serious complications and may lead to sections of the bowel having to be removed, although this is more common with CD. The presenting symptoms of IBS and IBD can be similar. Distinguishing them on clinical signs and symptoms can be difficult. Until recently, colonoscopy was often required to rule out IBD. In younger people, > 60% of colonoscopies showed no abnormality. Faecal calprotectin (FC) is a protein released by the white blood cells, neutrophils, found in inflamed areas of the bowel in IBD. Determining the level of FC in stool samples may help distinguish IBS from IBD. Objective: To review the value of FC for distinguishing between IBD and non-IBD. Data sources: Sources included MEDLINE, EMBASE, The Cochrane Library, Web of Science, websites of journals and the European Crohn’s and Colitis Organisation (conference abstracts 2012 and 2013), and contact with experts. Review methods: Systematic review and economic modelling. Review Manager (RevMan) version 5.2 (The Cochrane Collaboration, The Nordic Cochrane Centre, Copenhagen, Denmark) was used for most analysis, with statistical analyses done in Stata version 12 (StataCorp LP, College Station, TX, USA). Forest plots and receiver operating characteristic curves were produced. Quality Assessment of Diagnostic Accuracy Studies was used for quality assessment. Economic modelling was done in Microsoft Excel 2010 (Microsoft Corporation, Redmond, WA, USA). Limitations: Studies were often small, most used only one calprotectin cut-off level, and nearly all came from secondary care populations. Results: Twenty-eight studies provided data for 2 × 2 tables and were included in meta-analyses, with seven in the most important comparison in adults (IBS vs. IBD) and eight in the key comparison in paediatrics (IBD vs. non-IBD). Most studies used laboratory enzyme-linked immunosorbent assay (ELISA) tests. For distinguishing between IBD and IBS in adults, these gave pooled sensitivity of 93% and specificity of 94% at FC cut-off level of 50 µg/g. Sensitivities at that cut-off ranged from 83% to 100%, and specificities from 60% to 100%. For distinguishing between IBD and non-IBD in paediatric populations with ELISA tests, sensitivities ranged from 95% to 100% at cut-off of 50 µg/g and specificities of 44–93%. Few studies used point-of-care testing but that seemed as reliable as ELISA, though perhaps less specific. The evidence did not provide any grounds for preferring one test over others on clinical effectiveness grounds. FC testing in primary care could reduce the need for referral and colonoscopies. Any quality-adjusted life-year gains are likely to be small because of the low prevalence of IBD and the high sensitivities of all of the tests, resulting in few false negatives with IBD. However, considerable savings could accrue. Areas of uncertainty include the optimum management of people with borderline results (50–150 µg/g), most of whom do not have IBD. Repeat testing may be appropriate before referral. Conclusions: Faecal calprotectin can be a highly sensitive way of detecting IBD, although there are inevitably trade-offs between sensitivity and specificity, with some false positives (IBS with positive calprotectin) if a low calprotectin cut-off is used. In most cases, a negative calprotectin rules out IBD, thereby sparing most people with IBS from having to have invasive investigations, such as colonoscopy. Study registration: PROSPERO CRD 42012003287. Funding: The National Institute for Health Research Health Technology Assessment programme.